Multiscale Simulations of Biological Membranes: The Challenge To Understand Biological Phenomena in a Living Substance - Enkavi, Giray; Javanainen, Matti; Kulig, Waldemar; Róg, Tomasz; Vattulainen, Ilpo (Chemical reviews, 2019)
Biological membranes are tricky to investigate. They are complex in terms of molecular composition and structure, functional over a wide range of time scales, and characterized by nonequilibrium conditions. Because of all of these features, simulations are a great technique to study biomembrane behavior. A significant part of the functional processes in biological membranes takes place at the molecular level; thus computer simulations are the method of choice to explore how their properties emerge from specific molecular features and how the interplay among the numerous molecules gives rise to function over spatial and time scales larger than the molecular ones. In this review, we focus on this broad theme. We discuss the current state-of-the-art of biomembrane simulations that, until now, have largely focused on a rather narrow picture of the complexity of the membranes. Given this, we also discuss the challenges that we should unravel in the foreseeable future. Numerous features such as the actin-cytoskeleton network, the glycocalyx network, and nonequilibrium transport under ATP-driven conditions have so far received very little attention; however, the potential of simulations to solve them would be exceptionally high. A major milestone for this research would be that one day we could say that computer simulations genuinely research biological membranes, not just lipid bilayers.
Keywords: Lipidomics; Animals; Computer Simulation; biologické modely; lidé; fosfolipidy; kyseliny karboxylové; zvířata; Carboxylic Acids; Membranes; Models, Biological; Membrane Lipids; lipidomika; Phospholipids; počítačová simulace; membránové lipidy; membrány; Humans